OMXH15 entities’ application of principles and requirements of GRI in sustainability reporting - Junnikkala, Outi (2023)
The purpose of this study is to evaluate the extent the sustainability reports of OMXH15 listed entities apply the GRI principles and requirements, and thus potentially signal more positive image of their activities than is justified.